PURIFICAREA ŞI CARACTERIZAREA PARŢIALĂ A PROTEINAZEI A DIN SEMINŢELE GERMINATE DE FASOLE - USM ADMIN (Studia Universitatis Moldaviae: Stiinte reale si ale naturii, 2007)
Proteinase A, that possibly participate in the degradation of phaseolin, the main 7S storage protein of kidney bean (Phaseolus vulgaris L.), was isolated as a 35-kDa polypeptide from germinating kidney bean seeds and partially characterised. According to its properties it belong to a group of homologous cysteine proteinases of the papain family that participate in storage protein mobilisation during seeds geminating of many plants. The proteinases of this group hydrolize storage proteins to short peptides. Dispite close similarity to proteinase A from vetch, proteinase A from kidney bean hydrolyse phaseolin by non-co-operative mechanism. This action is limited to the cleavage of subunits into two approximately equal parts and to spliting off a number of short peptides which result in the modification of quaternary structure of phaseolin molecule. It is similar to the action on phaseolin of other proteases, both endogenous and exogenous, and provide another example of the importance of phaseolin structure in the explanation of its resistance to proteolysis.